2012
DOI: 10.1093/jscr/2012.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer after prophylactic mastectomy for Lobular Carcinoma-In-Situ (LCIS) - an unusual case

Abstract: Bilateral risk reducing mastectomy results in the greatest breast cancer risk reduction but is an irreversible intervention. Total mastectomy can never remove all breast tissue and there is always a small risk of breast cancer. Regular follow up and surveillance is beneficial. We present the case of a 47-year-old woman who presented with axillary lymph node metastatic breast cancer after risk reducing mastectomy in which only Lobular Carcinoma-in-Situ (LCIS) was present on histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There is a 4.3% recurrence rate of carcinoma after modified radical mastectomy. [17][18][19][20][21][22][23][24][25] This case highlights the importance of regular screening with annual mammogram in patients with a history of lobular cancer even more than 10years after bilateral mastectomies. Carcinomas arising in residual breast tissue may behave aggressively, including even those with low grade histology.…”
Section: Following Simple Mastectomy Residual Breast Tissue Is Presentmentioning
confidence: 77%
“…There is a 4.3% recurrence rate of carcinoma after modified radical mastectomy. [17][18][19][20][21][22][23][24][25] This case highlights the importance of regular screening with annual mammogram in patients with a history of lobular cancer even more than 10years after bilateral mastectomies. Carcinomas arising in residual breast tissue may behave aggressively, including even those with low grade histology.…”
Section: Following Simple Mastectomy Residual Breast Tissue Is Presentmentioning
confidence: 77%
“…We have planned to subject the patient to radiotherapy to achieve better loco regional control, as the margins of ectopic breast tissue may not be well defined. Gurjar et al 16 reported development of malignancy in axilla 21 months after a patient had undergone prophylactic mastectomy for lobular carcinoma in situ (LCIS). This suggests that remaining normal breast tissue or ectopic breast tissue is still susceptible to development of malignancy.…”
Section: Discussionmentioning
confidence: 99%